(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Additive manufacturing (AM) of drug delivery systems (DDS) is a promising tool for the development of patient-tailored treatments to ensure exact formation of individual scaffolds with specific incorporated drug combinations and concentrations. This study describes a novel hybrid AM process, combining stereolithography and inkjet printing, for printing a basic Polyethylene Glycol Diacrylate (PEGDA) DDS body and placing the model drug acetylsalicylic acid (ASA) in different drug depot locations. Adjusting the drug release by drug depot positioning according to drug diffusion is being investigated. The drug release rates from first 3D printed samples are being shown.